Health-related quality of life determinants among Rwandan women after delivery: does antenatal care utilization matter? A cross-sectional study - Regis Hitimana; Lars Lindholm; Gunilla Krantz; Manasse Nzayirambaho; Jeanine Condo; Jean Paul Semasaka Sengoma; Anni-Maria (BMC, 2018)
Abstract Background Despite the widespread use of antenatal care (ANC), its effectiveness in low-resource settings remains unclear. In this study, self-reported health-related quality of life (HRQoL) was used as an alternative to other maternal health measures previously used to measure the effectiveness of antenatal care. The main objective of this study was to determine whether adequate antenatal care utilization is positively associated with women's HRQoL. Furthermore, the associations between the HRQoL during the first year (1-13 months) after delivery and socio-economic and demographic factors were explored in Rwanda. Methods In 2014, we performed a cross-sectional population-based survey involving 922 women who gave birth 1-13 months prior to the data collection. The study population was randomly selected from two provinces in Rwanda, and a structured questionnaire was used. HRQoL was measured using the EQ-5D-3L and a visual analogue scale (VAS). The average HRQoL scores were computed by demographic and socio-economic characteristics. The effect of adequate antenatal care utilization on HRQoL was tested by performing two multivariable linear regression models with the EQ-5D and EQ-VAS scores as the outcomes and ANC utilization and socio-economic and demographic variables as the predictors. Results Adequate ANC utilization affected women's HRQoL when the outcome was measured using the EQ-VAS. Social support and living in a wealthy household were associated with a better HRQoL using both the EQ-VAS and EQ-5D. Cohabitating, and single/unmarried women exhibited significantly lower HRQoL scores than did married women in the EQ-VAS model, and women living in urban areas exhibited lower HRQoL scores than women living in rural areas in the ED-5D model. The effect of education on HRQoL was statistically significant using the EQ-VAS but was inconsistent across the educational categories. The women's age and the age of their last child were not associated with their HRQoL. Conclusions ANC attendance of at least four visits should be further promoted and used in low-income settings. Strategies to improve families' socio-economic conditions and promote social networks among women, particularly women at the reproductive age, are needed.